2005
DOI: 10.1002/j.2162-6057.2005.tb01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Artistic and Scientific Creative Behavior: Openness and the Mediating Role of Interests

Abstract: The arts and sciences have been identified as two specific domains that are dependent upon the creative process. A total of 369 undergraduate students served as research participants in two separate studies. In the first study, participants (N = 238) completed a measure of Openness to Experience (NEO‐PI; McCrae & Costa, 1999) and a questionnaire assessing artistic and scientific creativity (ASAS; Guastello & Shissler, 1994). Results from study 1 indicated that the Aesthetics and Actions personality traits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…The only personality dimension found with consistent correlation through the creativity assessment was the quality of openness. Many other studies have researched this very relationship and found similar results (George & Zhou, 2001;Wutrich & Bates, 2001;Furham, 1999;Perrine & Brodersen, 2005).…”
Section: ) Openness To Experience and Originalitysupporting
confidence: 60%
See 1 more Smart Citation
“…The only personality dimension found with consistent correlation through the creativity assessment was the quality of openness. Many other studies have researched this very relationship and found similar results (George & Zhou, 2001;Wutrich & Bates, 2001;Furham, 1999;Perrine & Brodersen, 2005).…”
Section: ) Openness To Experience and Originalitysupporting
confidence: 60%
“…Since traditional tests are primarily concerned with divergent thinking, some of the more whole-picture creativity measures set forth in the TCT-DP do not have direct links to the traditional measures. As such, Jellen and Bugingo (1989) (Guilford, 1967a;Guilford, Creativity, 1950;Guilford, Three faces of intellect., 1959;Cropley, 2000;Clapham, 1997;Clapham & Schuster, 1992;Runco, Millar, Acar, & Cramond, 2010;Kim, 2011 Need to explore and understand the known and unknown (Harrison, 2016;Hunter, Abraham, Hunter, Goldberg, & Eastwood, 2016;Windahl, 2017;Litman, 2005) Ne New Elements Originality Ability to generate novel ideas (George & Zhou, 2001;Wutrich & Bates, 2001;Furham, 1999;Perrine & Brodersen, 2005;Dollinger, Urban, & James, 2004;Feist, 2010) Ability to coalesce multiple ideas into one (Runco & Nemiro, 1994;Belski, 2009;English, 1997;Lai, Roan, Greenberg, & Yang, 2008;Ozyurt & Ozyurt, 2015;Wakefield, 1985;Rostan, 1994 Capacity for emotional transference (Genco, Johnson, Holtta-Otto, & Conner Seepersad, 2011;Chan & Schunn, 2014;Gardner & Winner, 1982;Piirto, 2004;Kohn, Paulus, & Korde, 2011;Mednick, 1962 Ability to take action in the face of the unknown (Eisenman, 1987;Pankove & Kogan, 1968;Sternberg, 2012;Steele...…”
Section: Evaluating Creativitymentioning
confidence: 99%
“…This indicates that individuals in this study who were higher 407 on Intellect were less likely to be interested in the fine or performing arts pursuits. This 408 finding is in line with that of Perrine and Brodersen (2005), who found that the Ideas facet 409 was a predictor of scientific rather than artistic pursuits. 410…”
Section: Results and Discussion 378supporting
confidence: 81%
“…Their measure has been used by many researchers in other management [44] and educational contexts [7] and also to further the work on CreaSE itself [19].…”
Section: Crease Research Findingsmentioning
confidence: 99%
“…After identifying the subconstructs above from literature on creativity [22,7,9,10,13,36,44,53], and before actually generating the constructs, we surveyed IS executives contacted through the advisory boards of two universities and IS faculty across four universities. The survey included two openended questions designed to gather valid content from both educators and professionals in the IS field.…”
Section: Item Generation and Content Validitymentioning
confidence: 99%